MANAJEMEN BENCANA DALAM PENDIDIKAN: ANALISIS LITERATUR SISTEMATIS TERHADAP PRAKTIK DI INDONESIA - Mulyani, Desi Sri; Habibi, Fauzan Nabil; Kurniawan, Yoga Cahya; Setiawan, Edi (JRPA - Journal of Regional Public Administration, 2025)
This research aims to systematically analyze the literature related to disaster management practices in the education sector in Indonesia. Indonesia is one of the countries with a very high level of disaster vulnerability, so disaster education is one of the essential strategies for disaster risk reduction efforts. The method used was a systematic literature review with a qualitative approach, referring to the PRISMA and PICOC methods, by reviewing eight relevant scientific articles published between 2010-2024. The results showed that integrating disaster education into the curriculum, particularly the Merdeka Curriculum, has allowed schools to develop contextualized learning according to local conditions. Sound practices are found at various levels, ranging from early childhood education with a game-based approach to high school with the role of adolescents as agents of change. However, implementation still faces challenges, 1such as limited supporting facilities, teaching modules, and teacher training. Cross-sectoral synergy is needed so that disaster education can run optimally and sustainably. This research recommends that disaster education be positioned as a significant component in developing disaster-resilient education, not just complementing the curriculum.